The 1990s and the Remaking of the Neoconservative Foreign Policy Paradigm - Awale, Rasha (Hungarian Journal of English and American Studies, 2022)
This essay explains how neoconservative foreign policy doctrine evolved from strenuously seeking to defeat the communist enemy during the Cold War to thoroughly seeking to preserve America’s newfound “unipolar moment” by constructing new enemies to defeat. It analyzes the generational transition within the neoconservative movement from the 1970s to the 1990s and its empire-building project in the post-Cold War era. Based on neoconservative publications and contributions to magazines such as Commentary, The National Interest, and Weekly Standard as well as the publications, reports, and statements of neoconservative think tanks (The Coalition for a Democratic Majority, The Committee on the Present Danger, American Enterprise Institute, The Project for New American Century, among others), the essay argues that the themes associated with the neoconservatives after 9/11—such as militarism, preemptive war, regime change, democratization, and unilateralism—had been rooted in the neoconservative discourse since the 1970s. It also shows that the post-9/11 neoconservative foreign policy approach was the product of neoconservative narratives during the Cold War era and after the fall of communism. (RA)